Pengaruh Electronic Money, Gaya Hidup Dan Pengendalian Diri Terhadap Perilaku Konsumsi Islam - Maulidysneni Nurvita Sukma; Clarashinta Canggih (ITB AAS INDONESIA Surakarta, 2021)
This study was aimed to reveal the impact of electronic money, lifestyle and self control towards Islamic consumption behaviour pattern of Y and Z generation in Surabaya. The behaviour pattern of Islamic consumption was measured by 6 basic principles of consumption in Islam. Descriptive quantitative was applied as the research method. This study took 150 respondents as the research sample by using the formula of Malhotra. The data was collected by using questionnaire along with purposive sampling method and guttman scales. Then, probit regression analysis using the application of Stata 14 was occupied as the data analysis. It was resulted that the variable of electronic money had a marginal effect value of -9,5% so that the probability was not correspond to the Islamic consumption behaviour pattern whereas the variable of life style had a value of -9% which meant that the probability was not correspond to Islamic consumption behaviour pattern and the variable of self control indicated a value of 17% so that the probability matched with Islamic consumption behaviour pattern